VO2 Max and Back and Leg Muscle Strength Profile of Universitas Padjadjaran Swimming Team - Pajar, Pitriyani Nurul; Farenia, Reni; Kuswiyanto, Rahmat Budi (Althea Medical Journal, 2016)
Background: Cardiorespiratory endurance (VO2 max) and back and leg muscle strength are a few components required to support the performance of swimming athlete during competition. The objective of this study was to determine the VO2 max and back and leg muscle strength in high category level of Universitas Padjadjaran swimming team period 2014. Methods: A descriptive study was conducted to 19 swimmers of Universitas Padjadjaran in September 2014. The variables of this study were VO2 max and back and leg muscle strength. Then, the data were categorized based on the standard of The National Sports Committee of Indonesia.Results: The data obtained showed that the VO2 max of the majority of subjects was in the very good category (6/19 subjects) and the back muscle strength of the majority of subjects was in the very good category (10/19 subjects). In contrast, the leg muscle strength of majority of subjects was in the low category (11/19 subjects).Conclusions: The VO2 max and back muscle strength in high category level of the swimming team fulfilled the standard of The National Sports Committee of Indonesia. [AMJ.2016;3(4):499â502]Â DOI:Â 10.15850/amj.v3n4